PENGARUH PENGGUNAAN TEPUNG DAUN KELOR (Moringa oleifera L.) DAN BEKATUL TERHADAP PERTUMBUHAN BURUNG PUYUH (Coturnix-coturnix japonica T.) SEBAGAI SUMBER BELAJAR BIOLOGI PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN - I Nyoman Sukaredana; Agus Sujarwanta; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
The aims of this study are 1) To determine the effect of the use of a mixture of moringa leaf flour and rice bran on the growth of quails (Coturnix-coturnix japonica T), 2) To find out a good variation of feed for the growth of quails, 3) To find out whether the results of this study can be used as a source of learning biology for growth and development material in class XII in the form of student worksheets (LKPD). This research was an experiment, using a Completely Randomized Design (CRD) with 1 control, 3 treatments, and 6 replications, with P0: (Control) treatment of quail feed in the form of pellet feed BR 21, P1: treatment of supplementary feeding in the form of a mixture of moringa leaf flour 3%, 47% bran and BR 21 50% pellets, P2: additional feeding treatment in the form of a mixture of 4% Moringa leaf flour, 46% bran, and 50% BR 21 pellets, P3: Additional feeding treatment in the form of 5% Moringa leaf flour 45% bran and BR 21 50% pellets. This research was conducted in the Iringmulyo sub-district, Metro Timur, Metro City, from 20 December 2019 until 1 February 2020. Based on the results of research the influence effect of the use of a mixture of moringa leaf flour and rice bran on the growth of quails (Coturnix-coturnix japonica T), it can be concluded that there is no increase body weight and length in quails, with the results of research on average weight P0 = 33,63 gram, P1 = 44,9 gram, P2 = 40,93 gram, P3 = 38,06 gram and the average length result data P0 = 10,06 cm, P1 = 11,4 cm, P2 = 10,5 cm, P3 = 10,46 cm. The results of this study can be used as a source of biology learning on the material for growth and development of class Xll in the form of a Student Worksheet (LKPD). The results of the validation of learning resources by experts' material and experts' design concluded that the Student Worksheet (LKPD) made by researchers was worthy to be used as a learning resource with an average score of 86,25 experts' material and 83,6 experts' design.